NORMATIVE JURIDICAL ANALYSIS OF PRESIDENTIAL REGULATION NUMBER 137 OF 2024 - Ramadani, Iko; Saragih, Yasmirah Mandasari; br. Sembiring, Tamaulina; Ismed, Ismed; Manurung, Krismanto (Hukum tata Negara/Siyasah, 2025)
ABSTRACTIndonesia as a democratic country has experienced various leadership dynamics that affect political, economic, and social development. As a country based on a presidential system. In accordance with the provisions of the 1945 Constitution of the Republic of Indonesia, the President of the Republic of Indonesia holds the highest government power and is assisted in carrying out his duties by the Vice President and state ministers. As time goes by, the President's support system continues to develop. In addition to the Vice President and ministries that have been regulated in the 1945 Constitution of the Republic of Indonesia, non-structural institutions such as the Special Advisor to the President, Special Envoy to the President, Special Staff to the President, and Special Staff to the Vice President have emerged which were formed based on Presidential Regulation Number 137 of 2024 concerning Special Advisers to the President, Special Envoys to the President, Special Staff to the President, and Special Staff to the Vice President. This study is a normative juridical research with a legal and regulatory approach and aims to deeply examine the roles and positions of the Special Advisor to the President, Special Envoy to the President, Special Staff to the President, and Special Staff to the Vice President in running the government.Keywords : President, Minister, Special Envoy of the President